Combined optical, EISCAT and magnetic observations of the omega bands/Ps6 pulsations and an auroral torch in the late morning hours: a case study - Safargaleev, V.; Sergienko, T.; Nilsson, Hans; Kozlovsky, A.; Massetti, S.; Osipenko, S.; Kotikov, A. (HAL CCSD, 2005)
International audience We present here the results of multi-instrument observations of auroral torch and Ps6 magnetic pulsations, which are assumed to be the magnetic signature of the spatially periodic optical auroras known as omega bands. Data from TV and ASC cameras in Barentsburg and Ny Ålesund, EISCAT radars in Longyearbyen and Tromsø, as well as IMAGE network were used in this study. The auroral phenomenon which was considered differed from that previously discussed, as it occurred both in an unusual place (high latitudes) and at an unusual time (late morning hours). We show that this might occur due to specific conditions in the interplanetary medium, causing the appropriate deformation of the magnetosphere. In such a case, the IMF turned out to be an additional factor in driving the regime of Ps6/omega bands, namely, only by acting together could a substorm onset in the night sector and B z variations result in their generation. Since the presumable source of Ps6/omega bands does not co-locate with convection reversal boundaries, we suggest the interpretation of the phenomena in the frame of the interchange instability instead of the Kelvin-Helmholtz instability that is widely discussed in the literature in connection with omega auroras. Some numerical characteristics of the auroral torch were obtained. We also emphasize to the dark hole in the background luminosity and the short-lived azimuthally-restricted auroral arc, since their appearance could initiate the auroral torch development. Keywords. Magnetospheric physics (Auroral phenomena; Plasma convection; Solar wind-magnetosphere interaction)